2020
DOI: 10.1101/2020.07.10.20150599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diaper need is associated with risk for food insecurity in a statewide sample of WIC participants

Abstract: Diaper need is a form of material hardship that acutely affects families with young children, is not currently addressed by US antipoverty programs, and has received little public or scientific attention. This study examined the association between diaper need and risk for food insecurity in a statewide sample of participants in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC). Families enrolled in Vermont WIC in August 2019 were invited to an online survey. Generalized linear… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Aligning with the prepandemic research of Belarmino et al and supporting the in-depth qualitative work of Randles, 6 , 37 the findings of this study highlight the creative and difficult tradeoffs that those with diaper need make to access enough diapers. While most households without diaper need accessed enough diapers by purchasing them with their own money, households with diaper need utilized multiple inventive and time-intensive strategies to access diapers.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Aligning with the prepandemic research of Belarmino et al and supporting the in-depth qualitative work of Randles, 6 , 37 the findings of this study highlight the creative and difficult tradeoffs that those with diaper need make to access enough diapers. While most households without diaper need accessed enough diapers by purchasing them with their own money, households with diaper need utilized multiple inventive and time-intensive strategies to access diapers.…”
Section: Discussionsupporting
confidence: 84%
“…Aligning with prior research, we found diaper need to be higher among caregivers who were Latino, 5 had limited education, 5 were unemployed, 5 had mental health challenges, 3 , 24 or lived in low-income, 5 or food insecure households. 3 , 6 The associations between diaper need and income remained significant after adjustment.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations